Professional pressure among kindergarten teachers (Journal of the College of Basic Education, 2022)
The current research aims to identify professional pressures related to business, and the main research sample consisted of (250) female teachers, randomly selected, Ministry of Education in Baghdad AL-Rusafa the First for the academic year (2020/2021).In order to achieve the objectives of the research, the researcher prepared the professional pressures, then analyzed the scale paragraphs of the logic of Theya and statistically to calculate its discriminatory ability and its validity coefficients.And the researcher verified the apparent validity of Al-Banna's validity to Al-Muqtib on the relationship (135) of the Cronbach's stability coefficient (89.0, 746.0) respectively. Thus, the scale is in the final form of (27) paragraphs of five alternatives which are (apply to me, apply to me, apply to me, apply to me), and reached the following results:- The value of the calculated main T (301, 8) is greater than the large T value (196, 1), which means that there are significant differences in degrees between the degrees and the hypothetical mean of the scale and this difference between the grades of higher degrees to kindergarten teachers with a high level of stress Professional.